Chinese Market Gardening in Australia and New Zealand - Boileau, Joanna. author. aut Link
XIX, 327 p. 18 illus.
Keywords: This book offers a fresh perspective on the Chinese diaspora. It is about the mobilisation of knowledge across time and space, exploring the history of Chinese market gardening in Australia and New Zealand. It enlarges our understanding of processes of technological change and human mobility, highlighting the mobility of migrants as an essential element in the mobility and adaptation of technologies. Truly multidisciplinary, Chinese Market Gardening in Australia and New Zealand incorporates elements of economic, agricultural, social, cultural and environmental history, along with archaeology, to document how Chinese market gardeners from subtropical southern China adapted their horticultural techniques and technologies to novel environments and the demands of European consumers. It shows that they made a significant contribution to the economies of Australia and New Zealand, developing flexible strategies to cope with the vagaries of climate and changing business and social environments which were often hostile towards Asian immigrants. Chinese Market Gardening in Australia and New Zealand will appeal to students and scholars in the fields of the Chinese diaspora, in particular the history of the Chinese in Australasia; the history of technology; horticultural and garden history; and environmental history, as well as Asian studies more generally.